Key Concepts for Informed Health Choices: a framework for helping people learn how to assess treatment claims and make informed choices. Issue 1 (24th January 2018) - Chalmers, Iain; Oxman, Andrew D; Austvoll-Dahlgren, Astrid; Ryan-Vig, Selena; Pannell, Sarah; Sewankambo, Nelson; Semakula, Daniel; Nsangi, Allen; Albarqouni, Loai; Glasziou, Paul; Mahtani, Kamal; Nunan, David; et al.
Abstract : Many claims about the effects of treatments, though well intentioned, are wrong. Indeed, they are sometimes deliberately misleading to serve interests other than the well-being of patients and the public. People need to know how to spot unreliable treatment claims so that they can protect themselves and others from harm. The ability to assess the trustworthiness of treatment claims is often lacking. Acquiring this ability depends on being familiar with, and correctly applying, some key concepts, for example, that' association is not the same as causation.' The Informed Health Choices (IHC) Project has identified 36 such concepts and shown that people can be taught to use them in decision making. A randomised trial in Uganda, for example, showed that primary school children with poor reading skills could be taught to apply 12 of the IHC Key Concepts. The list of IHC Key Concepts has proven to be effective in providing a framework for developing and evaluating IHC resources to help children to think critically about treatment claims. The list also provides a framework for retrieving, coding and organising other teaching and learning materials for learners of any age. It should help teachers, researchers, clinicians, and patients to structure critical thinking about the trustworthiness of claims about treatment effects.